2022
DOI: 10.52728/ijtc.v3i2.462
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Exchange of Information Review from the Perspective of its Effectives in Minimizing Tax Evasion

Abstract: This research aims to review the implementation of automatic exchange of information (AEoI) from the perspective of its effectiveness in minimizing tax evasion and to analyze the inhibiting entities and encouraging entities in AEoI in minimizing tax evasion. The research approach used in this study is a qualitative approach with data collection techniques using in-depth interviews, observation, literature/ documentation studies and source triangulation. The results of the study conclude that the Implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Muhammad Kifni said tax avoidance activities have caused state revenues from the tax sector not to reach the target and even if left unchecked, the state could lose hundreds of billions of tax revenues every year (Head of Sub-Directorate for Investigation of DJP) (Kifni, 2011) (Mappadang, 2020), mentions that tax evasion activities also occur in Indonesia for multinational companies engaged in the manufacturing industry. Likewise, (Pohan et al, 2022), stated that the practice of tax avoidance is usually carried out by parties who have special relationships both at home and abroad. (Desai & Dharmapala, 2006), found that the imposition of high tax rates forced companies to take tax avoidance actions.…”
Section: Introductionmentioning
confidence: 99%
“…Muhammad Kifni said tax avoidance activities have caused state revenues from the tax sector not to reach the target and even if left unchecked, the state could lose hundreds of billions of tax revenues every year (Head of Sub-Directorate for Investigation of DJP) (Kifni, 2011) (Mappadang, 2020), mentions that tax evasion activities also occur in Indonesia for multinational companies engaged in the manufacturing industry. Likewise, (Pohan et al, 2022), stated that the practice of tax avoidance is usually carried out by parties who have special relationships both at home and abroad. (Desai & Dharmapala, 2006), found that the imposition of high tax rates forced companies to take tax avoidance actions.…”
Section: Introductionmentioning
confidence: 99%